2013
DOI: 10.1016/j.profoo.2013.04.021
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Feasibility of Utilizing the Automated Self-administered 24-hour (ASA24) Dietary Recall in a Sample of Multiethnic Older Adults

Abstract: The ASA24 is a web application which enables the collection of self-administered dietary recalls thus utilizing technology to overcome some of the limitations of traditional assessment methodologies. Older adults, particularly those from certain ethnic groups may have less access to and may be less receptive to technology. This research sought to determine the level of access to the internet as well as evaluate the feasibility of using a web-based alternative dietary data collection method in older, multiethni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 19 publications
3
17
0
Order By: Relevance
“…In contrast, Carter et al observed a lower SUS score for myfood24-UK in older adults (median SUS score = 29, n = 4 ≥ 65 years old) compared to younger age groups [5]. Further, feasibility testing for ASA24 in two different samples of elderly individuals showed that participants mostly preferred the traditional telephone-administered 24HDR [29] and the SUS score of 57 (SD 12.4, ASA24-Canada-2014) indicated poor usability [30]. The authors presumed that low computer literacy and limited Internet access narrow the ability to conduct self-administered 24HDRs online in older adults [29][30][31].…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…In contrast, Carter et al observed a lower SUS score for myfood24-UK in older adults (median SUS score = 29, n = 4 ≥ 65 years old) compared to younger age groups [5]. Further, feasibility testing for ASA24 in two different samples of elderly individuals showed that participants mostly preferred the traditional telephone-administered 24HDR [29] and the SUS score of 57 (SD 12.4, ASA24-Canada-2014) indicated poor usability [30]. The authors presumed that low computer literacy and limited Internet access narrow the ability to conduct self-administered 24HDRs online in older adults [29][30][31].…”
Section: Discussionmentioning
confidence: 92%
“…Further, feasibility testing for ASA24 in two different samples of elderly individuals showed that participants mostly preferred the traditional telephone-administered 24HDR [29] and the SUS score of 57 (SD 12.4, ASA24-Canada-2014) indicated poor usability [30]. The authors presumed that low computer literacy and limited Internet access narrow the ability to conduct self-administered 24HDRs online in older adults [29][30][31]. Our contrasting findings might be explained by the fact that only participants with Internet access were included in the evaluation study, and that the majority of participants had experience in using computers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Informal feedback from participants highlighted issues with the user-friendliness of the system, technological barriers to completing recalls, and limitations of food selection options. A previous study using the Beta version of ASA24 in older adults (55 to 80 years) also found technology literacy to be a barrier for implementation and half of the participants preferred a traditional 24HR over ASA24 [ 19 ]. Since completion of the CLSA Diet Study, an updated version of ASA24-Canada was released in Fall 2016 including a French version and an improved interface that overcomes some of the technological issues in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Only one study examined the feasibility of the ASA24 in a sample of older adults (using a beta-version), and reported substantial challenges related to internet access and technology literacy. More research is needed to assess the usability of current versions of automated dietary assessment tools among older populations [ 19 ].…”
Section: Introductionmentioning
confidence: 99%